Identitas Tionghoa Muslim Indonesia Pasca-Orde Baru: Melampaui Batas-Batas Kategori Peranakan dan Totok - Afthonul Afif (Antropologi Indonesia, 2012)
The dramatic change in some important aspects of this country after the collapse of New Order Regime, primarily in the political aspect, provided larger opportunity to Indonesian Chinese in constructing their real identity, included to the Indonesian Chinese Muslim. In one hand, Indonesian Chinese Muslim tended to re-strengthen their cultural identity shown by articulating some features of their ethnic identity, and they show more the involvement in developing discourse of national building and the life of majority group by using their Islamic identity in the other hand. At this point, they then could not be categorized as ‘peranakan’ and ‘totok’, the binary category which is often used to refer to the asimilated and unasimilated Chinese into the cultural system practized by the native majority. After the state launched the new regulation of citizenship No. 12/2006, they were then positioned by the state as the ‘real’ citizen who had the same civil rights before the law as well as the other groups. The implication of this legacy in the social and cultural context is that they then developed the inclusive identity, such as absorbing the categories and features of identity of other group, involved in the activities of majority group, and occupied the same kind of majority group profession, until they felt that those had become part of their own identity. By sharing their identity with non-Muslim Chinese and majority group, they could take a strategic role as cultural mediators, political brokers and bridge builders. Keywords: Chinese Muslim, Identity, Peranakan, Totok, Hibridity, Post-New Order Indonesia.